Remineralizing potential of CPP-ACP in white spot lesions - A systematic review - K Indrapriyadharshini; P D Madan Kumar; Khushbu Sharma; Kiran Iyer (Wolters Kluwer Medknow Publications, 2018)
Objective: The aim of this systematic review was to assess the long term remineralizing potential of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) only in paste form compared with fluoride varnish, and or placebo in both naturally occurring and post-orthodontic white spot lesions in vivo. Data Sources: The literature search covered the electronic databases: PubMed and Google scholar from 2005-2016. Only articles published in English were included. Randomized control trials in which CPP-ACP delivered by paste form were included. All studies which met inclusion criteria underwent two independent reviews. Study Selection: Two ninety five articles were identified from the search after excluding duplications. Abstracts of forty one articles were reviewed independently. Twenty nine articles were excluded after reading abstract. Full text articles were retrieved for fifteen relevant studies. After reviewing articles independently, three articles were excluded after full text reading. Finally twelve studies were selected based on the eligibility criteria. The remineralizing effect of CPP-ACP were compared with placebo and fluoridated toothpaste and fluoride varnish in randomized control trial. Conclusion: A high level evidence of remineralizing potential of CPP-ACP on naturally occurring white spot lesion and WSL post orthodontic treatment was found in comparison with placebo/fluoridated toothpaste and fluoride varnish without any statistically significant difference. Well-designed RCTs are, therefore, required to improve the level of evidence in this area.